TRADISI BHANTI-BHANTI: MEMORI KOLEKTIF ORANG WAKATOBI TENTANG MALUKU - Udu, Sumiman (Himpunan Sarjana Kesusastraan Indonesia, Komisariat Sulawesi Tenggara, 2022)
bhanti-bhanti Tradition, Collective Memory, Wakatobi-Maluku Wakatobi people have a collective memory of Maluku as the brother country of their ancestors. But on the other hand, they also have a collective memory about the country of Sanggila (the nickname for Ternate and Tobelo) which always comes to arrest the people of Wakatobi Buton to be used as slaves who are traded in the country of Maluku. Therefore, their collective memory is in the tension between traumatize and romanticism. Research on collective memory will be carried out through an ethnographic perspective, so that it is hoped that it will be able to capture the various perspectives of the Wakatobi people about Maluku. Ethnographic data will be traced through bhanti-bhanti texts that have grown and developed within the Wakatobi community as their collective memory. Furthermore, field data will be obtained from the Wakatobi community, which so far has been integrated with the Maluku people. The results of this study indicate that the Wakatobi people have some collective memories about traumatic matters in the history of their relationship with Maluku, but on the other hand they also have a long romantic history with their relatives from Maluku.